The Effect of Job Satisfaction, Work Environment and Workload on Employee Loyalty at PT True Prime Jakarta: English - Abdul Rahmat; Fajri Rasyidi (Dinasti International Journal of Management Science, 2023)
This study is to determine the effect of job satisfaction, work environment and workload on employee loyalty of PT. True Prime. The object of this research is all employees who work at PT. True Prime. This research was conducted on 48 respondents using a quantitative descriptive approach. Determination of sample size using a saturated sample technique that is taking the entire population. The approach used in this research is Structural Equation Model (SEM) with Smart-PLS analysis tool. Therefore, the results of this study state that the variable job satisfaction has a significant positive effect on employee loyalty, the work environment has a significant positive effect on employee loyalty and workload has a positive and significant effect on employee loyalty at PT. True Prime.